Treasure Island - Stevenson, Robert Louis (Penguin Books Harmondsworth, Middlesex, England, 1994)
Jim Hawkins, gets hold of a treasure map and sets off with an adult crew in search of the buried treasure. Among the crew, however, is the treacherous Long John Silver who is determined to keep the treasure for himself.